Competency-based Training in Health Sciences - Ramón Syr Salas Perea; María Luisa Quintana Galende; Grisell Pérez Hoz (Medisur)
The training and development of human capital is one of the priorities of the National Health System. This paper aims to present a reflection on the training of health professionals focusing on the competencies they need to perform successfully in their future workplaces, where they will be able to demonstrate in practice the integration between clinical care, teaching, and research. For this purpose, theoretical and empirical methods were used. It includes a logical-historical analysis of the competencies, as well as the bases for the development of the professional competencies required in the field of health. The processes for the operationalization of competency building and the sources of evidence that this process requires are proposed and described. The paper also presents a detailed analysis of the evaluation of student performance through the demonstration of attitudes, skills, and values in health settings, in addition to the procedures and sources of evidence for such evaluation. New methods and evaluation techniques are described to support the reflections on the use of competency-based training in Health Sciences.